Description Of Diabetic Wound Treatment With Hydrogel In Pedis Care Malang City - Triska Dama Yanti; Abdul Hanan; Lucia Retnowati; Eddi Sujarwo; Susi Milwati (Lembaga Pengembangan Kinerja Dosen, 2024)
The hydrogel's optimum hydration ability can lyse slough and necrotic tissue (autolytic debridement ability). This study aims to determine the description of diabetic wound care using hydrogel as a modern dressing in the development of BWAT scores. The research design uses a case study method and consisting of 2 samples with grade II-III diabetic ulcers at Pedis Care Malang. The results of the study on subject I obtained the BWAT score on the first treatment was 33 and on the sixth day of treatment was 26, in subject II the first treatment was 37 and on the sixth day of treatment was 25, showed a decrease in the BWAT score, which means that diabetic ulcer healing progressed. The healing process of diabetic ulcer wounds is also influenced by the nutrients that enter the body, one of which is protein which plays a role in cell formation. The researcher's advice for both subjects is that they are expected to be able to maintain wound moisture with sustainable modern dressings until the wound is declared healed and increase nutrition as a supporting factor for wound healing.